Employee Initiatives as Mediator of the Relationship Between Organizational Citizenship Behavior and Employee Performance - Febriana, Artha (Jurnal Penelitian Ekonomi dan Bisnis, 2022)
The study of the behavior of human resources in organizations is growing in line with the awareness that individual behavior has a positive effect on individual and organizational performance as a whole. Employee performance is influenced by many factors, including organizational citizenship behavior (OCB), organizational culture, and employee initiative. This study aims to examine the effect of organizational citizenship behavior (OCB) and organizational culture on employee performance with employee initiative as a mediating variable. This study uses a quantitative approach. The research sample used was 100 employees in the IT department with purposive sampling technique. Based on the results of partial regression analysis, it shows that OCB and organizational culture have a positive and significant effect on both employee initiative and employee performance. The higher the employee's initiative, the higher the employee's performance. Employee initiatives mediate the relationship between OCB and organizational culture with employee performance.Keywords: OCB, organizational culture, employee initiative, and employee performance.